2023
DOI: 10.1039/d3sc01698f
|View full text |Cite
|
Sign up to set email alerts
|

Restriction of intramolecular rotation for functionalizing metal nanoclusters

Abstract: The restriction of intramolecular rotation has been extensively exploited to trigger the property enhancement of nanocluster-based materials. However, such a restriction was induced mainly by the intermolecular aggregation, the direct...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…Indeed, both intramolecular and intermolecular interactions could restrict the vibration/rotation of cluster molecules and further improve their molecular properties. [57][58][59][60][61] The intermolecular interactions (such as C-H⋯F, C-H⋯π, π⋯π) were widely discovered in nanoclusters, while the study of the restriction of intramolecular rotations was insufficient in metal nanoclusters. In this work, we demonstrated that ligand engineering could be an efficient surface control strategy for activating the intra-/inter-molecular interactions of metal nanoclusters, achieving the functionalization of cluster-based nanomaterials.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, both intramolecular and intermolecular interactions could restrict the vibration/rotation of cluster molecules and further improve their molecular properties. [57][58][59][60][61] The intermolecular interactions (such as C-H⋯F, C-H⋯π, π⋯π) were widely discovered in nanoclusters, while the study of the restriction of intramolecular rotations was insufficient in metal nanoclusters. In this work, we demonstrated that ligand engineering could be an efficient surface control strategy for activating the intra-/inter-molecular interactions of metal nanoclusters, achieving the functionalization of cluster-based nanomaterials.…”
Section: Resultsmentioning
confidence: 99%
“…Currently, several effective methods have been developed to fine-tune the nanocluster structures, including heterometal doping, 40–42 ligand engineering, 43–48 counter ion template, 49–52 and so on. The ligand engineering strategy is considered one of the most effective ways to regulate the structure and supramolecular assembly of nanoclusters.…”
Section: Introductionmentioning
confidence: 99%